Bovine Tuberculosis and the Multidrug Resistance of Mycobacterium - , Jashima Debbarma, J B Rajesh, Payel Kar, Manas Das, C Christen, Binipi Debbarma, Sherry Carelyne Marwein, Kh Thanila Rose, Elone Lucy, Ankita Debnath (Archives of Current Research International, 2025)
Bovine tuberculosis (bTB) caused Mycobacterium bovis, is a chronic infectious disease that primarily affects cattle and can affect other animals also. This zoonotic disease spread around the world, with the exception of Antarctica. Around fifty million cattle are suffering from bTB worldwide. This disease is highly significant to public health, leading to economic losses, especially in countries where livestock are the main source of livelihood. Aerosol mode of transmission is the most common way of infection in cattle and infection also can spread through contaminated material. bTB affected animals will show fluctuating low-grade temperature, weakness, gradual emaciation, decreased appetite and breathing difficulty, wet cough, or tachypnoea. The caseo-necrotic granuloma is the hallmark of TB and which is a process by the host to localize the disease and to allow immune and inflammatory mechanisms to act on bacilli. Treatment is not recommended for bTB due to its infectious nature. Due to its infectious nature, culling is often recommended as part of control strategies in many regions. The drug for treating bTB is Rifampin and Isoniazid. Mycobacterium bovis–BCG vaccination is used for bTB control in India.